Síntese de 1-(selenobutil)-2-fenil-4h-selenofeno[2,3-c]cromenos via reação de ciclização cascata mediada por FeCl3 - Silva, Guilherme Lutz da (2020)
The synthesis of heterocyclic compounds is of great importance within the chemistry of materials and the biological area, targeting both the chemical industry and the pharmaceutical industry. Among the different heteroatoms made up of these heterocycles, the selenium atom is capable of bringing different properties to these compounds, mainly in the pharmaceutical area, since most of these heterocyclic compounds contain biological activity. This work aims to synthesize chromene derivatives fused with selenophenes from 1,3-diinyl-aryl-propargyl ethers based on the treatment of these substrates with a mixture of iron (III) chloride and dibutyl diselenide. The same reaction conditions were applied to 1,3-diinyl-aryl-propargylanilines leading to the formation of selenophen quinolines. The reaction parameters were studied and the results obtained were applied to a series of substrates, providing the appropriate products that varied from 33 to 85% of yield. Mechanistic studies indicated that the cooperative action between iron (III) chloride and dibutyl diselenide was essential, having a double action, promoting cyclization and functionalization in the final product with a butylselenoate group. We also proved the synthetic utility of the heterocycles obtained in the Suzukitype cross-coupling reaction, providing the corresponding products coupled with good yields. In addition, the organoselenium portion can be removed from the product structure using n-butyl lithium. Therefore, this work proposed an efficient methodology for the production of twenty-five compounds never reported in the literature, considering a relatively cheap reaction condition with the use of additives that are not harmful to the environment.